Isoflavone supplementation reduces low-density lipoprotein cholesterol levels in postmenopausal women - Yenny Yenny; Pusparini Pusparini (Faculty of Medicine, Universitas Trisakti, 2013)
Background Cardiovascular disease is the main cause of death in postmenopausal women. This study aimed at evaluating the effect of soy isoflavone supplementation on plasma lipid profile in postmenopausal women, since this effect is still unclear. MethodsA double-blind randomized placebo-controlled trial was conducted from January 2010 until February 2011. In total 180 postmenopausal women were randomized into an isoflavone group and a control group of 90 subjects each. The isoflavone group received tablets containing 100 mg soy isoflavones and 500 mg calcium carbonate, while the control group received 500 mg calcium carbonate only. Supplementation was given once daily for 1 year. Plasma lipid levels [triacylglycerol, total, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) cholesterols] were assessed at baseline, and after 6 and 12 months of supplementation using an enzymatic colorimetric method (Cobas c 111, Roche). Independent t-test was used for data analysis. ResultsBaseline subject characteristics and lipid profile in the two groups were comparable. In the isoflavone and control groups after 6 months of supplementation LDL cholesterol levels were 124.9 ± 35.2 mg/dL vs 112 .7 ± 29.7 mg/dL (p=0.013*), respectively, and after 12 months 116.9 ± 31.7 mg/dL vs 109.1 ± 29.8 mg/dL (p=0.086). There were no significant differences in the other lipid levels at 6 and 12 months. Conclusions Soy isoflavone supplementation for 6 months was capable of significantly reducing LDL cholesterol levels in postmenopausal women. No significant changes in total cholesterol, triacylgycerol, and HDL cholesterol were found after isoflavone supplementation.